Behaviour of engineered cementitious composites and hybrid engineered cementitious composites at high temperatures. (15th January 2018) - Pourfalah, S.
Highlights: Behaviour of ECC and hybrid ECC subjected to compression load at high temperatures. Behaviour of ECC and hybrid ECC subjected to flexural load at high temperatures. Improve the integrity of ECC subjected to compression and flexural load at high temperatures using steel fibres. Using a finite element model to investigate the experimental results. . Abstract: The behaviour of engineered cementitious composites (ECC) specimens using polyvinyl alcohol (PVA) fibres and hybrid engineered cementitious composites (HECC) using PVA fibres and steel fibres (two different types) was experimentally investigated. The experiments included compression and flexural tests at different temperatures ranging from 20 °C to 600 °C. Under uniaxial compression load the HECCs specimens produced less debris (from 200 °C to 600 °C) compared to ECC counterparts. The flexural tests results revealed that the load bearing capacity and deflection of HECCs specimens were less vulnerable up to 100 °C compared to ECC specimens. Under higher temperatures the ECC specimens' behaviour was brittle, while HECCs specimens exhibited a deflection-softening behaviour. Then a finite element model was employed to investigate the flexural tests results obtained from experiments.